Europe in the world: EU geopolitics and the making of European space - Bialasiewicz L. (Ashgate Publishing Ltd, 2011)
This edited volume provides an innovative contribution to the debate on contemporary European geopolitics by tracing some of the new political geographies and geographical imaginations emergent within - and made possible by - the EU's actions in the international arena. Drawing on case studies that range from the Arctic to East Africa, the nine empirical chapters provide a critical geopolitical reading of the ways in which particular places, countries, and regions are brought into the EU's orbit and the ways in which they are made to work for 'EU'rope. The analyses look at how the spaces of 'EU'ropean power and actorness are narrated and created, but also at how 'EU'rope's discursive (and material) strategies of incorporation are differently appropriated by local and regional elites, from the southern shores of the Mediterranean to Eastern Europe and the Balkans. The question of EU border management is a particularly important concern of several contributions, highlighting some of the ways in which the Union's border-work is actively (re)making the European space. © Luiza Bialasiewicz 2011. All rights reserved.